If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -2 = 34 Reorder the terms: -2 + 3a = 34 Solving -2 + 3a = 34 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3a = 34 + 2 Combine like terms: -2 + 2 = 0 0 + 3a = 34 + 2 3a = 34 + 2 Combine like terms: 34 + 2 = 36 3a = 36 Divide each side by '3'. a = 12 Simplifying a = 12
| Z-4.5z+0.6=1.9(z+6) | | 3(a+4)-2(3a+4)=4a-1 | | ((42)180)+((((8)13)7)36)+((13)18)+8500= | | 5y^2-12y+8=0 | | -2x-5=-42 | | 2b+7=57 | | ln(9-3x)-2ln(x)=ln(2) | | 125+105+(x+50)+x=360 | | 10y=8y | | 7t+8=9t | | 15=-8b-1+9 | | 3y+58=2y | | 3x(x-2)=4x-3 | | 2b-4=8b-11 | | (-5x)+(-42x)= | | (2x-2)(2x-2)=26 | | -6(-8x+4)= | | -15y+5x=30 | | 16.37+(-29.786)=y | | 3x=.5x+11 | | 5+32t-16t^2= | | -5.642-2.57=m | | -3+5+x=15 | | 15y+5x=30 | | 1x(4-3)=14 | | 3.9-36.24=z | | .40x=.5x-12 | | 25.9+(-4.3)=z | | -6(-3x+3)= | | 2x-4(x-4)=-2+5x-24 | | 56-(3c+4)=(c+5)+c | | 7b-8b= |